Determinants of Strategic Management: an Analysis of Corporate Culture, Business Environment, Performance Measurement, Technological Change, and Leadership Style - Wahyu Putra, Christophorus Indra; Widyastuti, Tri (Green Publisher, 2025)
This literature research aims to help hypotheses for future authors in determining research related to strategic management. The research article determining strategic management: analysis of corporate culture, business environment, performance measurement, technological change, and leadership style is a scientific literature article on the scope of human resource management. The approach used in this literature review research is descriptive qualitative. Data collection techniques are using literature studies or reviewing relevant previous articles. The data used in this study are secondary data, which are sourced from academic online media such as Thomson Reuters Journals, Sage, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Springer, Web of Science, Sinta Journals, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Corporate Culture affects Strategic Management; 2) Business Environment affects Strategic Management; 3) Performance Measurement affects Strategic Management; 4) Technological Change affects Strategic Management; and 5) Leadership Style affects Strategic Management.